Influence Of Teaching Styles On Students’ Achievement And Interest Among Biology Students In Secondary Schools In Taraba State Nigeria - Audu, Christina Tanko (Advances in Social Sciences Research Journal, 2018)
The study investigated the influence of teaching styles on students’ achievement and interest in Biology in Secondary schools in Taraba state. The study was guided by two research questions and two hypotheses. The study adopted the survey and quasi experimental designs. A sample of 336 senior secondary two students from ten secondary schools was drawn using stratified sampling technique. The instrument used for data collection were the Biology Achievement Test (BAT) and Biology Interest Inventory developed by the researcher. Biology teachers in the selected schools were observed and their teaching styles were identified either as students centred or teacher centred using teaching style check list. The treatment was carried out in six weeks during which data were also collected at various intervals using the BAT and BII. The data collected were analyzed using mean and standard deviations to answer the two research questions while analysis of covariance (ANCOVA) was used in testing the two hypotheses at 0.05 level of significance. The findings indicated that there was a significant difference in the mean achievement scores of students’ taught Biology using student centred teaching styles and those taught using the teacher centred teaching styles with those taught using student centred teaching styles achieving higher. Also students who were taught Biology using student centred teaching styles had a higher interest rating than those taught using the teacher centred teaching styles. It was recommended that Biology teachers should use student centred teaching styles which provides students the opportunity to take charge of their learning and be actively involve thereby enhancing their achievement and interest and that ministry of Education should organize workshops/seminars to train in-service Biology teachers on how to use student centred teaching styles